Southern Ocean and Southern African Monsoon Forcing of the Subtropical Indian Ocean Early Pliocene ?Biogenic Bloom? - Tangunan, D. N.; Flores Villarejo, Jos? Abel; LeVay, L. J.; Jim?nez Espejo, Francisco J.; Coenen, J. J.; Berke, M. A.; de Azevedo, A. Q.; Fuertes Prieto, Miguel ?ngel; Gruetzner, J.; Starr, A.; Hall, I. R. (Paleoceanography and Paleoclimatology, 2024)
[EN]The Pliocene epoch emerges as a pivotal juncture in Earth's climatic evolution, characterized by pronounced warmth and elevated atmospheric carbon dioxide compared to contemporary levels. While the broader climatic context of the Pliocene has garnered attention, there remains an outstanding gap in detailed paleoclimate reconstructions of the early Pliocene, a new potential target for data?model intercomparison. Addressing this, we investigate the drivers of the early Pliocene ?Biogenic Bloom? and implications for nutrient dynamics and climate. By analyzing high?resolution biotic assemblage and geochemical records from the Agulhas Plateau, southwestern Indian Ocean (International Ocean Discovery Program, IODP Site U1475), we aim to elucidate the forcing and feedback mechanisms driving the early Pliocene marine ecosystems. We identify a distinct shift in coccolithophore assemblages at ?4.6 million years ago, characterized by a notable change in dominance between the larger and smaller Reticulofenestra and high abundances of Noelaerhabdaceae < 5 ?m. Our findings confirm the adaptive strategies of coccolithophore communities to prevailing environmental conditions, underscoring their evolutionary resilience by producing smaller coccoliths while increasing their abundances in a nutrient?replete ocean. Surface water dynamics, particularly the subtropical front migration and expansion of Southern Ocean waters, in combination with the southern African monsoon variability, emerge as key drivers of phytoplankton productivity during the early Pliocene. We posit that a weakened biological carbon pump, due to increased phytoplankton production driven by intense ocean circulation and mixing during the early Pliocene, served as a potential precursor to the subsequent middle Pliocene abrupt climate extremes. Ministerio de Ciencia, Innovaci?n y Universidades Grant RTI2018-099489-B-I00. European Union's Horizon 2020 Research and Innovation Programme. Marie Sklodowska Curie Grant Agreement No. 885498 European Consortium ...